The Economic Significance of the Jaglot-Skardu Road: A Qualitative Analysis - Shoaib Malik; Asif Abbas , (Dialogue Social Science Review (DSSR), 2025)
The Jaglot-Skardu Road (JSR) plays a crucial role in the economic development of the Gilgit- Baltistan region of Pakistan. This research explores its economic significance through a qualitative approach, focusing on trade, tourism, market access, and socioeconomic transformations. The study employs a detailed literature review and qualitative data collection methods, including interviews with local business owners, transporters, and community members. Findings suggest that the road has led to reduced transportation costs, increased tourism, and improved accessibility to essential services, thereby contributing to overall regional development. Additionally, the improved connectivity has facilitated the movement of goods and services, resulting in market stability, price control, and greater economic opportunities for small businesses and entrepreneurs. The road has also played a pivotal role in empowering marginalized communities, including women artisans and rural traders, by providing them with access to larger markets. Furthermore, the road's enhancement has improved access to education and healthcare, fostering broader social and economic progress. This study highlights the critical role of infrastructure in driving sustainable regional growth and underscores the need for continued investment in road maintenance and development to maximize economic benefits.